تفسير سورة الفاتحة لأبي الكلام آزاد تعريفه، أهميته وخصائصه : Introduction of Tafseer –o- Suratil-Fatih of Abul Kalam Azad, its importance and characteristics - Ansari, Ala ud din (Al-Irfan, 2024)
The research aims to know the Introduction, importance and characteristics of Tafseer of Surah Al Fatiha written by Maulana Abul Kalam Azad (1888-1958AD). As his tafseer of Surh Al-Fatiha is one of the famous, valuable and reliable Tafseer. Therefore, the researcher sought to clarify Introduction, importance and characteristics of Tafsser of Surah Al Fatiha, so that scholars and university students could benefit from them. The researcher applies the inductive method to collect the materials regarding the topic and the analytical method to study the subject and analyze to obtain the results that are the goal of the subject. Among the contributions of the research is the introduction, importance and charecteristics of Tafseer of Surah Al Fatiha, compiled by Abul Kalam Azad.